Feminine Leadership Style in Disaster Management at BPBD Bojonegoro - Widyaningsih, Alvira; Taufiq, Ahmad; Musta'ana, Musta'ana (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This study uses a feminine leadership approach to analyze women's leadership in disaster management at BPBD Bojonegoro. Men often dominate leadership in disaster management, but BPBD Bojonegoro is currently led by women, which raises questions about women's leadership in disaster management at BPBD Bojonegoro through a feminine leadership perspective. The elements of feminine leadership in this article include charismatic, team-oriented, and self-protective. The method used in the studty is descriptive with a qualitative approach. Data were obtained based on field studies through interviews, observations, and documentation with interactive analysis. This study aims to determine women's leadership in the public sector, especially in the context of leadership in disaster management. The results of this study indicate that women's leadership not only increases women's participation in disaster management but also provides a holistic and inclusive perspective in disaster mitigation and response strategies, creating a collaborative and harmonious work environment by aligning common goals for the benefit of the community in crises. The novelty of this research lies in the analysis from a feminine leadership perspective regarding female learders in disaster mangement at BPBD Bojonegoro, where most of the literatur on disaster management focuse on technical and procedural aspects, without considering women’s involment in dicision-making. The involvement of women in emergencies can help the pre-disaster process to post-disaster recovery through an inclusive approach carried out to the community. The conclusion of this study emphasizes the importance of empowering women in leadership positions to improve the quality of disaster management in Indonesia.